Heirlooms of the Everyday: The Material Performances of Slamet Gundono1. Issue 1 (11th February 2016) - ESCOBAR VARELA, MIGUEL
Abstract : Javanese actor, puppeteer and musician Slamet Gundono (1966–2014) created performances with everyday objects and materials (mud, dried grass, cooking utensils, condoms and food) in combination with conventions from wayang kulit puppetry. His performances were based on personal, often controversial, interpretations of well-known stories, from the Mahabharata epic to the nineteenth-century literary work Serat Centhini . By analysing three of his performances, I argue that Slamet Gundono's objects become temporarily endowed with the status of heirlooms ( pusaka ). Each of his performing objects is a non-spiritual pusaka that is used to take attention away from the spiritual quests that dominate traditional wayang . Gundono invokes everyday objects to focus on the more mundane, though urgent, questions of gender inequality, religious intolerance and environmental destruction.